Influence of relative pitch area (RPA) on the physical demands across late-stage age categories in elite academy soccer - Meulenkamp, V.; Huijgen, B.; Kempe, M. (Current Issues in Sport Science, 2026)
Introduction & Purpose: Small-sided games (SSGs) are widely used in soccer training to recreate the physical, technical and tactical demands of official matches within controlled environments (Morgans et al., 2014). Manipulating pitch size, player numbers, and rules, allows SSGs to develop these demands, especially physical performance (Bujalance-Moreno et al., 2019). The interaction of pitch size and player numbers can be quantified through the relative pitch area (RPA; m2*player-1) (Hill-Haas et al., 2011; Olthof et al., 2019). A larger RPA elicits greater total distance, high-speed running, and sprinting demands (Riboli et al., 2020). However, limited evidence exists on age-related differences in physical demands among late-stage academy players. Therefore, this study investigated age-related differences in physical performance between U18 and U21 elite academy players across SSG formats defined by RPA.